2021
DOI: 10.1186/s13048-021-00876-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and clinical significance of somatic oncogenic mutations in epithelial ovarian cancer

Abstract: Objective Epithelial ovarian cancer (EOC) is a heterogeneous disease with diverse clinicopathological features and behaviors, and its heterogeneity may be concerned with the accumulation of multiple somatic oncogenic mutations. The major goals of this study are to systematically perform the comprehensive mutational profiling in EOC patients, and investigate the associations between somatic mutations and clinicopathological characteristics. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 43 publications
1
19
1
Order By: Relevance
“…no. 4475346; Thermo Fisher Scientific, Inc.), which covers ~2,800 mutational hotspot regions from 50 cancer-associated genes, as previously described (13)(14)(15). Endometrioid carcinoma is preferentially associated with mutations in PTEN, KRAS, AT-rich interaction domain 1A (ARID1A), catenin β1 (CTNNB1) and PI3K catalytic subunit α (PIK3CA) as well as microsatellite instability, whereas serous (non-endometrioid, type II) carcinoma exhibits HER2 amplification and TP53 and PPP2R1A mutations (16), which were assessed in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…no. 4475346; Thermo Fisher Scientific, Inc.), which covers ~2,800 mutational hotspot regions from 50 cancer-associated genes, as previously described (13)(14)(15). Endometrioid carcinoma is preferentially associated with mutations in PTEN, KRAS, AT-rich interaction domain 1A (ARID1A), catenin β1 (CTNNB1) and PI3K catalytic subunit α (PIK3CA) as well as microsatellite instability, whereas serous (non-endometrioid, type II) carcinoma exhibits HER2 amplification and TP53 and PPP2R1A mutations (16), which were assessed in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of PIK3CA mutations varies across different histological subtypes of OC; while these mutations are rare in high‐grade ovarian serous carcinoma (HG‐OSC) and ovarian mucinous carcinoma (OMC), they have been observed in >40% of cases of ovarian clear cell carcinoma (OCCC) and ovarian endometrioid carcinoma (OEC) 27–29 . PI3K pathway activation including the PIK3CA mutation was associated with favorable prognosis in OCCC 30,31 .…”
Section: Somatic Mutated Genes In Gynecological Cancermentioning
confidence: 99%
“…PI3K pathway activation including the PIK3CA mutation was associated with favorable prognosis in OCCC 30,31 . A recent study reported that PIK3CA mutations were significantly associated with favorable progression‐free survival (PFS) in OC, especially in the OEC subtype 29 . Although larger prospective cohort studies are needed for evaluation, activation of PIK3CA may be a useful biomarker.…”
Section: Somatic Mutated Genes In Gynecological Cancermentioning
confidence: 99%
“…Very few also harbor mutant PPP2R1A. 77 , 111 , 112 , 132 An elevated frequency of KRAS mutation in the human tissue specimens was hypothesized as the rationale for the chemoresistance and aggressiveness of EnOC. 133 A previous study also demonstrated the significant prevalence of the overexpression and amplification of KRAS gene in the aggressive phenotypes compared to the primary lesions.…”
Section: Introductionmentioning
confidence: 99%